2023
DOI: 10.1111/apha.13912
|View full text |Cite
|
Sign up to set email alerts
|

WNT/β‐catenin pathway is a key regulator of cardiac function and energetic metabolism

Abstract: The WNT/β‐catenin pathway is a master regulator of cardiac development and growth, and its activity is low in healthy adult hearts. However, even this low activity is essential for maintaining normal heart function. Acute activation of the WNT/β‐catenin signaling cascade is considered to be cardioprotective after infarction through the upregulation of prosurvival genes and reprogramming of metabolism. Chronically high WNT/β‐catenin pathway activity causes profibrotic and hypertrophic effects in the adult heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 300 publications
2
12
0
Order By: Relevance
“…Nineteen Wnt proteins have been identified in mammals. Among them, Wnt1, Wnt3a, Wnt7a, Wnt7b, Wnt 8 and Wnt 10a act as ligands to activate the canonical Wnt/β-catenin pathway ( Balatskyi et al, 2023 ). Wnts require glycosylation and palmitoylation to acquire the ability to be secreted, and these factors act in both an autocrine and paracrine manner.…”
Section: The Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%
See 4 more Smart Citations
“…Nineteen Wnt proteins have been identified in mammals. Among them, Wnt1, Wnt3a, Wnt7a, Wnt7b, Wnt 8 and Wnt 10a act as ligands to activate the canonical Wnt/β-catenin pathway ( Balatskyi et al, 2023 ). Wnts require glycosylation and palmitoylation to acquire the ability to be secreted, and these factors act in both an autocrine and paracrine manner.…”
Section: The Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%
“…β-Catenin was confirmed to affect the development and function of the heart by participating in the metabolism of cardiomyocytes ( Balatskyi et al, 2020 ; Balatskyi et al, 2021 ). A recent review showed that β-catenin could affect perinatal cardiometabolic maturation by altering glucose and fatty acid utilization ( Balatskyi et al, 2023 ). β-catenin ablation caused mitochondrial insufficiency in perinatal cardiomyocytes, and hearts with heterozygous β-catenin ablation failed to increase mitochondrial numbers in response to exercise training ( Balatskyi et al, 2020 ; Balatskyi et al, 2021 ).…”
Section: The Role Of β-Catenin In Cardiac Development and Functionmentioning
confidence: 99%
See 3 more Smart Citations